Futuristic evaluation of building energy simulation model with comparison of conventional villas. Issue 1 (2nd January 2022) - Krishnaraj, L.; Kumar, V.R. Prasath; Balasubramanian, M.; Kumar, Naveen; Shyamala, T
Abstract: Sustainability is always a goal in all major industries. Thus, this article speaks about the effective utilization of energy in the construction industry. Green building advancements include an integrated approach for maintainable objectives and to improve productivity, such green building's expense may be higher but the payback period can be reduced very much through reduced operation and energy costs. The approach for increasing the efficiency of the building is made through daylight analysis, the feasibility of fresh air ventilation system instead of aid conditioned space, rainwater harvesting system, analysis for suitability of low flow water fixture in buildings were done with the aid of tools such as eQUEST, ECOTECH and Daylight analysis tools. The data which is required for this analysis is obtained through the Building Management System. Also, the conventional buildings and the sustainable building (green building model) designed through this analysis were compared, as a result, it is obvious that the green building model done through this analysis possess characteristics such as reduced energy usage and increased efficiency. This will ultimately increase the value of the buildings.